Electrospinning polypropylene with an amino acid as a strategy to bind the antimicrobial peptide Cys-LC-LL-37 - Nogueira, Frederico (2017)
Hospital isolation gowns are increasingly competitive, with brands and manufacturers contesting consumer preferences. The textile materials in contact with the skin can acquire secretions and multiresistant microorganisms, causing discomfort and health risks, respectively. A new nanofibrous substrate— polypropylene grafted with L-Cys—was developed with an increased crystallinity, providing its surface with –SH hooks necessary to efficiently cross-link the antimicrobial peptide Cys-LC-LL-37 in order to protect against nosocomial pathogens and their spread to community. Furthermore, this application does not require environmental control of humidity, and it is not susceptible to enzyme and microorganism degradation.